Proactive post-occupancy evaluation - Rasheed E; Rotimi J; Vilasini N; Weerasinghe A (Build Magazine, 2021)
A digital post-occupancy evaluation system for checking the operational performance of commercial buildings will be a useful tool as New Zealand faces the need to meet stringent carbon targets.